Export (0) Print
Expand All

7.2.1 Operator precedence and associativity

Visual Studio .NET 2003

When an expression contains multiple operators, the precedence of the operators controls the order in which the individual operators are evaluated. For example, the expression x + y * z is evaluated as x + (y * z) because the * operator has higher precedence than the binary + operator. The precedence of an operator is established by the definition of its associated grammar production. For example, an additive-expression consists of a sequence of multiplicative-expressions separated by + or - operators, thus giving the + and - operators lower precedence than the *, /, and % operators.

The following table summarizes all operators in order of precedence from highest to lowest:

Section Category Operators
Section 7.5 Primary
x.y  f(x)  a[x]  x++  x--  new
typeof  checked  unchecked

Section 7.6 Unary
+  -  !  ~  ++x  --x  (T)x
Section 7.7 Multiplicative
*  /  %
Section 7.7 Additive
+  -
Section 7.8 Shift
<<  >>
Section 7.9 Relational and type testing
<  >  <=  >=  is  as
Section 7.9 Equality
==  !=
Section 7.10 Logical AND
&
Section 7.10 Logical XOR
^
Section 7.10 Logical OR
|
Section 7.11 Conditional AND
&&
Section 7.11 Conditional OR
||
Section 7.12 Conditional
?:
Section 7.13 Assignment
=  *=  /=  %=  +=  -=  <<=  >>=  &=  ^=  |=

When an operand occurs between two operators with the same precedence, the associativity of the operators controls the order in which the operations are performed:

  • Except for the assignment operators, all binary operators are left-associative, meaning that operations are performed from left to right. For example, x + y + z is evaluated as (x + y) + z.
  • The assignment operators and the conditional operator (?:) are right-associative, meaning that operations are performed from right to left. For example, x = y = z is evaluated as x = (y = z).

Precedence and associativity can be controlled using parentheses. For example, x + y * z first multiplies y by z and then adds the result to x, but (x + y) * z first adds x and y and then multiplies the result by z.

Show:
© 2014 Microsoft